PERANCANGAN MOBIL RAMAH LINGKUNGAN YANG MENDUKUNG AKTIFITAS EXTREME DI MEDAN GURUN - Marpaung, Jhon Viter (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Cars with environmentally friendly energy use as a driving force are already on the market. Various car segments have begun to be designed as a form of human seriousness in answering market desires and also human and environmental needs. But in fact, the design The design of a car that supports extreme touring activities with an adult desert or Sahara field can now be spelled out as still a little that supports the use of environmentally friendly renewable energy. The use of renewable energy is still limited to the application of urban cars. While the development of technology will open up many human needs in exploring their environment according to their interests and lifestyle.